Considerations for continued expansion of the Brazilian post-graduate system - McManus, Concepta; Baeta Neves, Abilio Afonso; Carvalho, Carlos Henrique; Souza Filho, Antonio Gomes; Freire, Denise Maria Guimarães; Fioravanti, Maria Clorinda Soares; Báo, Sônia Nair; de Medeiros, Isac Almeida; Diniz Filho, José Alexandre; Diaz, Bruno Lourenço; de Carvalho, Ernani Rodrigues; Audy, Jorge Luís Nicolas; et al. (Frontiers in Education, 2023)
The number of programs and students in the Brazilian postgraduate system has doubled in the last 10 years. This has implications for quality and financing of these programs, as well as for the development of the regions where they are set. This study aims to investigate the reasons and limitations for the continued expansion of the Brazilian postgraduate system. Data for this article included the number of postgraduate programs, lecturers and students, as well as financing for their studies, were collected from the government postgraduate database (Sucupira). Questionnaires were answered by the postgraduate deans of Higher Education Institutions (HEIs). Data analyses included regression over time, frequency chi squared and correspondence analyses. Different types of institutions in different regions showed varying opinions, with higher expectations for expansion in smaller, newer institutions, especially private ones. The HEIs in the North region believe that the master's degree is to correct undergraduate flaws. On the other hand, the HEIs in the South and Central regions and the community believe that the master's degree should develop professional skills. In contrast, the larger HEIs with older postgraduate programs in all regions believe in direct doctorate strategy. The reasons for creating new post-graduate programs involved following the institution's general guidelines for private and community HEIs and lecturers' wishes or constant expansion for federal, North, Northeast and Central regions, as well as medium-sized state universities. State of the art and interests of society was prevalent for the largest and oldest HEIs. Continued expansion of the Brazilian postgraduate system needs to take into account factors including the demand for the program, regionalization, the quality of the programs, the means of funding, the student vacancies existing in programs with high grades, among others challenges.